2003
DOI: 10.1093/carcin/bgg143
|View full text |Cite
|
Sign up to set email alerts
|

Liver tumorigenicity of trimethylarsine oxide in male Fischer 344 rats--association with oxidative DNA damage and enhanced cell proliferation

Abstract: Arsenic is a notorious environmental toxicant known to be carcinogenic for the skin, lung and urinary bladder in human beings. The carcinogenicity of trimethylarsine oxide (TMAO), one organic metabolite of inorganic arsenics in humans and experimental animals, was investigated here in male Fischer 344 rats in a 2-year carcinogenicity test. TMAO was administered to a total of 129 male rats ad libitum at concentrations of 0 (Control), 50 or 200 p.p.m. in the drinking water. In animals that died or were killed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 48 publications
3
51
0
Order By: Relevance
“…We further showed that hydroxyl radicals, generated through a superoxide-mediated process involving hydrogen peroxide, play an important role in mediating the genotoxic effects of arsenic (13). These findings are consistent with the reports stipulating the functional role of oxidants in mediating the biological effects of arsenite by linking glutathione content (14), heme oxygenase (15,16), oxidative DNA damage (12,17), and metallothionine (18) to the end points being examined. However, the origin of these oxyradical species and the pathways involved in the generation of other secondary radical species are not known.…”
Section: Introductionsupporting
confidence: 88%
“…We further showed that hydroxyl radicals, generated through a superoxide-mediated process involving hydrogen peroxide, play an important role in mediating the genotoxic effects of arsenic (13). These findings are consistent with the reports stipulating the functional role of oxidants in mediating the biological effects of arsenite by linking glutathione content (14), heme oxygenase (15,16), oxidative DNA damage (12,17), and metallothionine (18) to the end points being examined. However, the origin of these oxyradical species and the pathways involved in the generation of other secondary radical species are not known.…”
Section: Introductionsupporting
confidence: 88%
“…In addition, two methylated arsenicals containing As V (dimethylarsinic acid and trimethylarsine oxide) are complete carcinogens in rats. [9,10] Hence, the conversion of iAs to methylated metabolites is an activation process [11] and methylated arsenicals derived from the metabolism of other arsenicals should be considered in assessing the risk associated with exposure to these arsenicals. (1), (3), (5), and (7) convert As V to As III and Reactions (2), (4), and (6) are oxidation methylation reactions.…”
Section: David J Thomas Is Research Toxicologist In the Experimentalmentioning
confidence: 99%
“…As noted above, trimethylarsine oxide is a liver carcinogen in rats. [10] AS3MT catalyzes conversion of trimethylarsine oxide to trimethylarsine, [7] a volatile genotoxic species. [22] Chickens treated with arsenocholine exhale a strong garlic-like odor consistent with trimethylarsine expiration; [23] thus, the chicken orthologue of mammalian AS3MT gene (J. Li et al, in preparation) may catalyze the final reductive step in this pathway.…”
Section: Trimethylarsonium Compoundsmentioning
confidence: 99%
“…Methylated pentavalent arsenicals, methylarsonic acid (MAs V ), dimethylarsinic acid (DMAs V ), and TMAs V O, which are less acutely toxic than either arsenate (iAs V ) or arsenite (iAs III ) (Yamauchi and Fowler, 1994), are thought to be detoxification products. However, unlike iAs species, DMAs V and TMAs V O at high doses are complete carcinogens in adult rats (Shen et al, 2003;Wei et al, 1999). In contrast, methylated trivalent arsenicals, methylarsonous acid (MAs III ) and dimethylarsonous acid (DMAs III ), are more toxic than iAs in vivo (Petrick et al, 2001) and are more potent than iAs as enzyme inhibitors (Lin et al, 2001;Petrick et al, 2001;, cytotoxins (Petrick et al, 2000;Styblo et al, 2000, and as modulators of cell signaling pathways (Drobná et al, 2003;.…”
Section: Introductionmentioning
confidence: 99%